Opiates Modulate Noxious Chemical Nociception through a Complex Monoaminergic/Peptidergic Cascade - Mills, Holly (J Neurosci, 2016)
The ability to detect noxious stimuli, process the nociceptive signal, and elicit an appropriate behavioral response is essential for survival. In Caenorhabditis elegans, opioid receptor agonists, such as morphine, mimic serotonin, and suppress the overall withdrawal from noxious stimuli through a pathway requiring the opioid-like receptor, NPR-17. This serotonin- or morphine-dependent modulation can be rescued in npr-17-null animals by the expression of npr-17 or a human κ opioid receptor in the two ASI sensory neurons, with ASI opioid signaling selectively inhibiting ASI neuropeptide release. Serotonergic modulation requires peptides encoded by both nlp-3 and nlp-24, and either nlp-3 or nlp-24 overexpression mimics morphine and suppresses withdrawal. Peptides encoded by nlp-3 act differentially, with only NLP-3.3 mimicking morphine, whereas other nlp-3 peptides antagonize NLP-3.3 modulation. Together, these results demonstrate that opiates modulate nociception in Caenorhabditis elegans through a complex monoaminergic/peptidergic cascade, and suggest that this model may be useful for dissecting opiate signaling in mammals. SIGNIFICANCE STATEMENT Opiates are used extensively to treat chronic pain. In Caenorhabditis elegans, opioid receptor agonists suppress the overall withdrawal from noxious chemical stimuli through a pathway requiring an opioid-like receptor and two distinct neuropeptide-encoding genes, with individual peptides from the same gene functioning antagonistically to modulate nociception. Endogenous opioid signaling functions as part of a complex, monoaminergic/peptidergic signaling cascade and appears to selectively inhibit neuropeptide release, mediated by a α-adrenergic-like receptor, from two sensory neurons. Importantly, receptor null animals can be rescued by the expression of the human κ opioid receptor, and injection of human opioid receptor ligands mimics exogenous opiates, highlighting the utility of this model for dissecting opiate signaling in mammals.